(untitled) (Research, Society and Development, 2021)
Objective: To analyze the impact of the COVID-19 pandemic on the mental health of health professionals in the municipality of Pinheiro. Methodology: Descriptive, quantitative and cross-sectional study, carried out with professionals involved in direct care to patients affected by COVID-19 in the municipality mentioned. Three instruments were used for data collection (a sociodemographic questionnaire; the Back-Bai anxiety inventory; and the Perceived Stress scale) compiled in a virtual form on the Google Formes platform, sent to participants through messaging applications. Results: The sample consisted of 73 professionals, of which 79.45% are women, 72.60% are Catholic, 78.08% receive up to 5 minimum wages, 49.31% are nursing professionals. About the experience of remarkable events in the last year, the majority of 50.05% denied it, however, 47.95% admitted this experience. In the Beck-Bai Anxiety Inventory it was observed that 45.21% were classified as minimal symptomatology, 23.29% mild, 17.81% moderate and 13.70% severe. Conclusion: Frequent exposure to contamination risks, major decision-making, long working hours, lack of personal protective equipment, loss of close colleagues or family members, are presented as considerable aggravating factors for the mental health of health professionals, and little the long-term consequences of this psychological suffering are know.